Computational studies on the Rh-catalyzed carboxylation of a C(sp2)–H bond using CO2. Issue 16 (25th July 2017) - Lv, Xiangying; Zhang, Linhui; Sun, Beibei; Li, Zhi; Wu, Yan-Bo; Lu, Gang
Abstract : CO2 insertion is facilitated by the critical effects of a Lewis acid and an agostic interaction. Abstract : The mechanism and effects of ligands and reagents in Rh-catalyzed C(sp 2 )–H bond carboxylation with CO2 were investigated using density functional theory (DFT) calculations. The catalytic cycle involves sequential C–H oxidative addition, CO2 insertion into the Rh–C(aryl) bond and transmetalation. Among these steps, CO2 insertion is the rate-determining step. In addition to its role as a methylation reagent, AlMe2 (OMe) can also serve as a Lewis acid to promote the CO2 insertion step. The greater reactivity of the catalyst with the bulkier P(Mes)3 ligand than that with PPh3 benefits from the favorable agostic interaction between the Rh center and the ortho -methyl group in the P(Mes)3 ligand, which can stabilize the transition state of CO2 insertion.